The Concept of Endogamous Marriage in Islamic Law: Study of Tafsir Al-Misbah by Quraish Shihab - Moh Syarifuddin; Jatim Jatim (Rechtenstudent, 2025)
Marriage is a sunnatullah for the entire universe. Allah SWT gave humans reason and heart, which makes them different from other loving creatures. Therefore, in human life there is something called marriage, which is recommended for every Muslim man and woman to avoid falling into sin. This is recommended for Muslims who are physically and mentally able to marry, so as not to fall into sin. In the modern era, endogamous marriage is rarely found in society. This is due to the development of the times. This study aims to determine the views of Quraish Shihab regarding endogamous marriage in the interpretation of Al-Misbah QS An-Nisa' verse 23. The research method used is a qualitative method by searching for data from several books and journals that are in accordance with the study of endogamous marriage.